Chemically active oil filter to develop detergent free bio-based lubrication for diesel engine. (1st April 2017) - Gulzar, M.; Masjuki, H.H.; Alabdulkarem, Abdullah; Kalam, M.A.; Varman, M.; Zulkifli, N.W.M.; Zahid, Rehan; Yunus, R.
Abstract: In diesel engine lubricants, over-based detergent additives are typically used to neutralize acids. These additives are required for long service life, but their use results in hazardous emissions, which mainly include sulfur and ash content. To address this problem, this study investigates the detergent-free bio-based lubricant conditioning approach by using a chemically active oil filter. A standard filter element impregnated with sodium oxide particles was used to improve lubricant quality. In this research, palm trimethylolpropane ester was synthesized for use as the base oil for formulation of a detergent-free bio-based lubricant. A condition-based approach, in which two engine endurance tests were carried out, was adopted. Lubricant samples from new and engine-aged conditions were tested for viscosity, total acid number, total base number, and corrosion. Piston ring-cylinder sliding tests were conducted to determine the wear protection and friction behavior of lubricant samples. A comparative analysis showed that lubricant conditioning by a modified filter improved the alkaline reserve and controlled the viscosity increase, thus extending the bio-based lubricant service life from 80 h to 200 h. The bio-based lubricant conditioned by a chemically active filter exhibited reduced cylinder liner wear and friction coefficient by 9.2% and 12.9%, respectively. Highlights: Potential of renewable and alternative base stock for diesel engine lubrication. Chemically active filter technology helped to develop detergent free lubrication. Reduction in viscous drag by low viscosity oil thus friction coefficient was lowered by 12.9%. Improvement in engine parts protection as 9.2% reduced cylinder wear rate was observed. For engine testing with modified filter, drain interval extended from 80 h to 200 h.